Information About a Layperson's Knowledge Supports Experts in Giving Effective and Efficient Online Advice to Laypersons. - Nückles, Matthias; Wittwer, Jörg; Renkl, Alexander (Journal of Experimental Psychology. Applied, 2005)
To give effective and efficient advice to laypersons, experts should adapt their explanations to the layperson's knowledge. However, experts often fail to consider the limited domain knowledge of laypersons. To support adaptation in asynchronous helpdesk communication, researchers provided computer experts with information about a layperson's knowledge. A dialogue experiment (N = 80 dyads of experts and laypersons) was conducted that varied the displayed information. Rather than sensitizing the experts to generally improve the intelligibility of their explanations, the individuating information about the layperson enabled them to make specific partner adjustments that increased the effectiveness and efficiency of the communication. The results are suggestive of ways in which the provision of instructional explanations could be enhanced in Internet-based communication. Reprinted by permission of the publisher.